Socio-demographic Characteristics and Behavioural Risk Factors in Selected Tribal Community in Bangladesh - Farah, Shayela; Karim, Mohoshina; Sultana, Masuda; Mahmud, Abdullah Al; Tahera, Sadiqa (Community Based Medical Journal, 2016)
Tribal and minority populations are increasingly exposed to risk factors as a result of urbanization. The study was conducted in the Rakhain community in Cox's Bazar district, Bangladesh, with the aims of determining the socio-demographic characteristics and behavioural risk factors. This cross-sectional study was done among 287 Rakhain individuals. Data were collected by face to face interview using pretested structured questionnaire. More than one third respondents were from the age group of 35-44 years. Their mean age was 40.66 (±11.275) years. Majority of the respondents were male 148(52%), married 222(77.4%) and educated up to primary level 179(62.4%). The highest proportion 68(23.7%) of the respondents were housewife and day laborer and lowest were unemployed 26(9.1%). Their average monthly family income were 17874.56 (±7208.553) Taka. Statistically significant association were found between their smoking status and socio-demographic characteristics (p <0.001). The high burden of behavioral risk factors in Rakhain community was observed in the present study. CBMJ 2016 January: Vol. 05 No. 01 P: 04-08